Greater sage‐grouse use of mechanical conifer reduction treatments in northwest utah. (11th March 2017) - Cook, Avery A.; Messmer, Terry A.; Guttery, Michael R.
ABSTRACT: A potential consequence of climate change, altered fire regimes, and a legacy of resource exploitation in western North America is increased displacement of desirable sagebrush ( Artemisia spp.) communities by invasive plant species. Annually, an estimated 90, 000 ha of sage‐grouse ( Centrocercus spp.) habitat is degraded by pinyon ( Pinus spp.) and juniper ( Juniperus spp.; PJ) encroachment. Sage‐grouse responses to conifer encroachment may include avoidance of otherwise available habitats, lek abandonment, and subsequent population declines. Thus, restoration of PJ encroached sage‐grouse habitats that exhibit intact sagebrush understories is a priority conservation action. However, better information is needed regarding sage‐grouse response to these management actions. We used sage‐grouse fecal pellet surveys and radiotelemetry location data to identify vegetation and landscape attributes that may influence sage‐grouse use of PJ removal treatments completed using mechanical methods. Use of PJ removal treatments by sage‐grouse was positively associated with irrigated pasture and alfalfa ( Medicago sativa ) hay within 1 km (β = 7.69, SE = 5.58, P = 0.17) and negatively associated with PJ canopy cover (β = −1.52, SE = 0.84, P = 0.07) within 500 m of treatments. Percent cover of mesic habitats and sagebrush canopy were greater within 1 km of treatments where sage‐grouse were detected; however, these relationships were weak because of large variability in conditions across sites. Our results document sage‐grouse use of 9 of 16 mechanical PJ removal treatments examined in an encroached sagebrush landscape and suggest that mechanical PJ removal treatments should be sited adjacent to occupied sage‐grouse habitat in areas that minimize surrounding PJ cover. © 2017 The Wildlife Society. Abstract : Expansion of conifer woodlands pose a threat to sage‐grouse populations, and large‐scale habitat improvement projects are being implemented to reduce conifer cover throughout sage‐grouse range. We investigated habitat characteristics associated with sage‐grouse use of project areas and found avoidance of conifer canopy cover at a 500 m scale.